La sociología del escritor y su contribución a la historia social de la literatura latinoamericana (2014)
ABSTRACT: The study of the writers’ work and their social and professional circles relates their condition to structures and social classes or groups with the purpose of giving explanations and analyses. From the empiricaldemonstrative observation of habits and actions (in bio-bibliographic legacies, literary tradition, files, and historical studies), it is possible to determine specific traits of writers eventually applicable to such a social-professional group in its interaction with social groups.